Adult Learning Models for Translational Health Research: Bench, Bedside, and Communities - Linda Ziegahn (Adult Education Research Conference, 2010)
The intent of translational health research is to bridge the longstanding gaps between laboratory research and the people who are the intended beneficiaries of the resulting discoveries. Models from the field of adult education, particularly experiential and transformative learning approaches, can be useful in developing theory for the learning processes that occur when scientists, health practitioners, and community members collaborate around the identification, implementation, and evaluation of research projects aimed at improving health for everyone.